Pharmacy students' attitude towards providing pharmaceutical care to patients with anxiety and their knowledge of psychotropic medicines in Jordan. (28th December 2020) - Al Jomaa, Esraa E; Abdel-Qader, Derar H; Silverthorne, Jennifer; Hamadi, Salim; Al Meslamani, Ahmad Z
Abstract: Objectives: To describe pharmacy students' attitude towards providing pharmaceutical care (PC) to patients with anxiety and their knowledge of psychotropic medicines (PM). Methods: A cross-sectional emailed survey was sent to all 200 pharmacy students (fourth and fifth year) in one Jordanian university. Statistical analysis included descriptive statistics and chi-square test. Key findings: A total of 134 responses were received (response rate 67%). About two-thirds of students (87, 64.9%) would like to give enough time to patients with anxiety to discuss their medications. Only half of students knew correctly that alprazolam (53.7%) and diazepam (50.0%) are categorized as anxiolytics. Undertaking a course in psychiatry was significantly associated with better students' knowledge in PM ( P < 0.05). Conclusion: Despite positive attitudes towards providing PC to patients with anxiety, policy makers should include courses on psychiatric pharmacotherapy in pharmacy curricula to improve pharmacy students' knowledge of PM.